2023
DOI: 10.1161/circep.122.010858
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Junctophilin 2 Expression in Cardiac Nodal Tissue Results in Intracellular Calcium-Driven Increase in Nodal Cell Automaticity

Abstract: BACKGROUND: Spontaneously depolarizing nodal cells comprise the pacemaker of the heart. Intracellular calcium (Ca 2+ ) plays a critical role in mediating nodal cell automaticity and understanding this so-called Ca 2+ clock is critical to understanding nodal arrhythmias. We previously demonstrated a role for Jph2 (junctophilin 2) in regulating Ca 2+ -signaling through inhibition of RyR2 (ryanodine rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Similar observations were recently reported by Landstrom et al in tamoxifen-inducible, pacemaker tissue-specific (Hcn4-targeted), junctophilin 2 knockdown mice (Hcn4:shJph2). 33 Junctophilin 2 provides a structural bridge between the sarcolemma and SR membranes in atrial and ventricular working myocytes, facilitating the functional coupling between LTCCs and RyR2 at dyadic junctions. 34 However, it remains unknown whether junctophilin 2 serves a similar function in pacemaker cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were recently reported by Landstrom et al in tamoxifen-inducible, pacemaker tissue-specific (Hcn4-targeted), junctophilin 2 knockdown mice (Hcn4:shJph2). 33 Junctophilin 2 provides a structural bridge between the sarcolemma and SR membranes in atrial and ventricular working myocytes, facilitating the functional coupling between LTCCs and RyR2 at dyadic junctions. 34 However, it remains unknown whether junctophilin 2 serves a similar function in pacemaker cells.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Moreover, the knockdown of junctophilin-2 (JPH2), which is abundant in the T-tubules has been described as interacting with the Ca 2+ -handling machinery via the RYR2 by provoking Ca 2+ -leak from the sarcoplasmic reticulum and inducing increased automaticity and arrhythmogenesis. 44 Consistent with these observations, in our model of right-sided atrial remodelling, we discovered that JPH2 was significantly decreased in RA from RHD rats compared to sham ( Figure 10 ).…”
Section: Discussionsupporting
confidence: 83%
“… 11 , 12 , 13 We have previously demonstrated that Jph2 knockdown in murine nodal cells causes increased automaticity of nodal cells owing to Ca 2+ leak from the SR in Hcn4:shJph2 mice. 14 These findings support a potential pharmacologic target for correction of Ca 2+ dysregulation. 15 Recently, a novel compound, 2-(diethylamino) ethyl 4-(butylamino)-2-methoxybenzoate (EL20) has been shown to decrease Ca 2+ leak from the SR through targeting RyR2 in ventricular cardiac myocytes.…”
mentioning
confidence: 58%
“…Compared with tamoxifen-treated control mice (Hcn4:WT mice), knockdown mice demonstrated an approximately 40% reduction of Jph2 transcript and protein expression. 14 These mice demonstrate no arrhythmias at rest nor inducible arrhythmias with intracardiac electrical stimulation, but rapid infusion of isoproterenol in ex vivo Langendorff perfused hearts consistently triggered a rapid AV-dissociated tachycardia; thus, we hypothesized that these mice could serve as an in vivo model of JET. 14 Initially, central venous isoproterenol and/or epinephrine injection via a customized lumened electrophysiologic catheter did not consistently trigger AV-dissociated tachycardia in vivo.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation